Cloning, bioinformatics analysis and expression of the cysteine dioxygenase type 1 (CDO1) gene in domestic yak - Fu, Yuxin; Yan, Jiuru; Lan, Lan; Zhang, Huizhu; Wang, Peng; Wang, Yaying; Xiong, Xianrong; Li, Jian; He, Honghong (Frontiers in Veterinary Science, 2024)
IntroductionThe CDO1 gene is an important gene in the taurine synthesis pathway and has been observed to have high expression in ovaries of female mammals. This study aims to explore the conservation of CDO1 gene in domestic yaks, as well as to examine the fundamental characteristics of CDO1 gene and its expression in female yaks.MethodsOvarian samples were collected from yaks in the follicular phase, luteal phase and gestation period in this experiment, and their total RNA and protein were extracted. Then Polymerase Chain Reaction (PCR) and bioinformatics online software were used to clone and analyze the CDO1 gene. The relative expression of CDO1 in yak ovaries was detected by Quantitative Real-time PCR (RT-qPCR) and Western blotting. The distribution and localization of CDO1 protein in ovary were detected by immunohistochemistry.ResultsWe have successfully cloned the coding region of CDO1 gene in yak. The results showed that the CDS region of CDO1 gene was 603 bp, encoding 200 amino acids, and was a relatively stable hydrophilic protein. CDO1 is relatively conservative in species evolution. The protein encoded by CDO1 gene does not have a signaling peptide or a transmembrane structure. It is a protein that is not involved in transmembrane transport and is mainly located in the cytoplasm. The secondary structure of the protein is dominated by the random coil. CDO1 is estimated to interact with 10 proteins. The results of RT-qPCR and Western blotting showed that the CDO1 gene exhibited the highest expression in the ovary during the luteal phase and the lowest expression in the ovary during the follicular phase (P < 0.01). The results of immunohistochemistry showed that CDO1 was mainly expressed in granular cells, theca cells and lutein cells of ovarian tissue.ConclusionThese results suggest that the CDO1 gene has undergone minimal evolutionary changes during the course of animal evolution. The results provide a reference for further investigation of the function of CDO1 gene in reproduction and production in yaks.